TREATMENT OF PURULENT-INFLAMMATORY DISEASES OF THE ABDOMINAL CAVITY WITH ANTIMICROBIAL THERAPY IN A MULTIDISCIPLINARY HOSPITAL (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article describes the experience of using antimicrobial therapy for the treatment of purulent-inflammatory processes of the abdominal cavity in a multidisciplinary emergency hospital. As part of the integrated approach, we used the fourth-generation fluoroquinolone (Lefloxacin) and the fourth-generation beta-lactam antibiotic cephalosporin (Cefepime-tazobactam), as well as the local antiseptic Dekasan for the treatment of abdominal infections of various etiologies. The clinical and pharmacoeconomic effectiveness of these methods is demonstrated.